Factor Influencing University Students’ Investment Interests: A Correlational Study - Dewa Ayu Oki Astarini; Ikang Murapi (Journal of Information System, Applied, Management, Accounting and Research, 2026)
The trend toward digital technology modernization has increased students’ investment interests. However, this has not been accompanied by adequate financial literacy, which could potentially lead to poor decision making. This quantitative study using a correlation analysis method, aims to analyze the influence of lifestyle, social environment, allowance, and self control on the motivation to invest among students at the faculty of economics and business Bumigora University. The population for this study consisted of 1.119 students and the sample size was determined using the Slovin formula to be 291 participants. Primary data obtained through a digital questionnaire was analyzed using multiple linear regression. The data analysis indicates that lifestyle, social environment, allowance, and self control have a positive significant on students investment interests. Collectively, these factors also act as strong determinants of students motivation in investing. The results of this study have practical implications for educational institutions in developing more targeted financial curricula, as well as for policymakers in developing more prudent and responsible investment initiatives.